Cardiac involvement in female elite athletes with carrier status of Duchenne muscular dystrophy - Wernhart, Simon; Kastner, Tom; Halle, Martin; Mueller, Stephan; Schmid, Veronika; Akbulut, Cihan; Wolf, Cordula M.; Meierhofer, Christian; Trenkwalder, Teresa; Diebold, Isabel; Herzog, Christopher; Brill, Richard; et al. (Frontiers in Cardiovascular Medicine, 2025)
Duchenne muscular dystrophy is a muscle-wasting, progressive, X-linked inherited disease in young male individuals, who—aside from peripheral muscular impairment—may also suffer from severe cardiac complications. In women who are muscular dystrophy carriers (MDCs), muscular symptoms and cardiac complications are less severe or even absent. While male individuals with muscular dystrophy are not usually able to perform strenuous exercise, women who are MDCs can exercise at mild, or even high, intensity. However, the impact of participating in elite sports, particularly endurance sports with high cardiopulmonary exercise strain, on female athletes who are MDCs is uncertain. Herein, we describe two rare cases of female elite athletes who are MDCs who participated in endurance sports. We describe their clinical presentation, kinetics of cardiac biomarkers and peripheral muscle enzymes during acute exercise, and cardiac manifestations in the context of sports eligibility, including an interdisciplinary shared decision-making approach to whether to continue participating in sports. This approach focuses on pathophysiology and genetics in dystrophinopathies, with a particular focus on genetic carrier status. While the primary concern is risk stratification for sudden cardiac death and its prevention, the potential risk of early onset of myocardial dysfunction or even heart failure also needs to be considered in MDCs. To optimize exercise recommendations, these complex and rare cases of athletes require an interdisciplinary approach, including experts in sports cardiology, sports medicine, radiology, and genetics, and should be included in a long-term international sports cardiology registry.